Potential of Herbaspirillum and Azospirillum Consortium to Promote Growth of Perennial Ryegrass under Water Deficit - Sandra Cortés-Patiño; Christian Vargas; Fagua Álvarez-Flórez; Ruth Bonilla; German Estrada-Bonilla (Microorganisms, 2021)
Plant growth-promoting bacteria (PGPB) can mitigate the effect of abiotic stresses on plant growth and development; however, the degree of plant response is host-specific. The present study aimed to assess the growth-promoting effect of Herbaspirillum (AP21, AP02), Azospirillum (D7), and Pseudomonas (N7) strains (single and co-inoculated) in perennial ryegrass plants subjected to drought. The plants were grown under controlled conditions and subjected to water deficit for 10 days. A significant increase of approximately 30% in dry biomass production was observed using three co-inoculation combinations (p < 0.01). Genomic analysis enabled the detection of representative genes associated with plant colonization and growth promotion. In vitro tests revealed that all the strains could produce indolic compounds and exopolysaccharides and suggested that they could promote plant growth via volatile organic compounds. Co-inoculations mostly decreased the in vitro-tested growth-promoting traits; however, the co-inoculation of Herbaspirillum sp. AP21 and Azospirillum brasilense D7 resulted in the highest indolic compound production (p < 0.05). Although the Azospirillum strain showed the highest potential in the in vitro and in silico tests, the plants responded better when PGPB were co-inoculated, demonstrating the importance of integrating in silico, in vitro, and in vivo assessment results when selecting PGPB to mitigate drought stress.